Straw board for floor slab and its manufacturing method and application

By crushing rice straw, ultrasonic treatment and soaking with various solutions, combining the addition of hydrophobic materials and modifiers, as well as spraying and molding processes of diphenylmethane diisocyanate adhesive, straw boards with high strength, hydrophobicity and fire resistance are prepared, which solves the shortcomings of existing boards in terms of strength, flame retardancy, etc.

CN111483032BActive Publication Date: 2025-04-01JIANGSU HEJI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010259161.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-04-03
Publication Date
2025-04-01
Estimated Expiration
2040-04-03

AI Technical Summary

Technical Problem

The existing straw boards have defects in strength, flame retardancy, acid and alkali resistance, water resistance and environmental protection. The main reasons are the large amount of adhesive used, the reduced structural strength, the low efficiency of the hot pressing process and the increase in the weight of the board.

Method used

By pulverizing the rice straw and soaking it in a variety of solutions, impurities are removed and the properties of cellulose are improved. Then hydrophobic materials and modifiers are added, and the adhesive spraying is used with diphenylmethane diisocyanate adhesive. Finally, pre-pressing and hot pressing are performed in a molding machine to prepare straw sheets with high strength, hydrophobicity and fire-repellency.

Benefits of technology

It achieves the improvement of the mechanical properties of the plate while reducing the amount of adhesive used, has hydrophobicity and fire resistance, is suitable for secondary processing and molding, and the product performance meets environmental protection and economic requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111483032B_ABST
    Figure CN111483032B_ABST
Patent Text Reader

Abstract

Straw board for floor slab and its manufacturing method and application, the rice straw is cleaned with water, and then crushed to obtain straw crushed material after drying; the straw crushed material is taken, stirred and washed in water; the washed straw is squeezed and dehydrated, and then dried; the straw crushed material is added to sodium hydroxide solution, ultrasonically soaked at room temperature, washed with water to be neutral, soaked in sulfuric acid solution at room temperature after draining, then hydrated to neutral, and then soaked in sodium silicate solution, finally dried to obtain straw fiber, and then hydrophobic material and modifier are added to the straw fiber; the obtained straw fiber is sent to a stirring type glue sprayer, a spray gun is set in the stirring type glue sprayer for glue spraying, and the straw fiber and the adhesive are stirred to be uniformly mixed; the straw fiber mixed with the adhesive is transferred to a molding machine, and pre-pressed and hot-pressed in the molding machine after paving to obtain a straw board. The present invention improves the mechanical properties of the board while reducing the amount of adhesive applied, and the product has hydrophobicity and fire resistance, which is convenient for secondary processing and molding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to a building board for floor slabs, and in particular to a straw board and a manufacturing method and application thereof. Background Art

[0002] As a byproduct of agricultural production, crop straw has long been treated as waste by farmers by burning and discarding it due to the lack of good processing and utilization, causing serious environmental pollution and great waste of fiber resources. The cellulose and lignin content of straw is relatively high. If it can be fully used, it can solve the severe environmental problems such as haze, sharp decline in forest resources, and excessive carbon emissions caused by burning straw. However, due to the constraints of various factors, the development of straw building materials has encountered bottlenecks and has not performed well in the market. At present, the research direction of straw boards is mostly focused on how to improve the bonding performance of straw and adhesives. In the prior art, researchers have made certain attempts to produce boards using crop straw, but the bonding performance of crop straw is poor, and it is difficult for ordinary matrix resins to penetrate into the interior of the straw, affecting the wetting, diffusion, and penetration of the matrix resin, making it difficult to produce qualified boards. In order to improve the performance of straw boards, it is necessary to use expensive isocyanate adhesives to improve the bonding strength, which greatly increases the production cost. Based on environmental protection and economic requirements, straw boards that do not use or use less adhesives should be more in line with the future development direction of boards. However, there are few studies in this area, and the product performance deteriorates after the amount of adhesive used is reduced. Although the existing technology has made certain attempts to use crop straw to produce boards, the products produced have some defects in strength, flame retardancy, acid and alkali resistance, water resistance and environmental protection. The main reasons are as follows: First, the adhesives currently used in the processing of artificial boards are mainly urea-formaldehyde resin adhesives (UF) and phenolic resin adhesives (PF). It is difficult to obtain satisfactory bonding strength with such adhesives, and in the production process of functional boards, especially in the preparation process of hydrophobic boards, simple mixing of hydrophobic materials often causes the structural strength of the boards to decrease and crack and loosen. Secondly, the traditional hot pressing process can be roughly divided into three stages, namely the slab compression stage, the gel reaction curing stage and the low-pressure exhaust stage. The hot pressing process is usually also the key control node in the manufacture of panels: first, the exhaust time is long, which is about one-third of the entire production process time, resulting in relatively low production efficiency; second, the slab is prone to bubbling during the exhaust process, which leads to a decrease in product qualification rate and increased costs. Third, in order to improve the strength of the panel, the existing technology usually adds cement to the core of the panel and lays materials such as cotton felt on the surface, but the weight of the panel will increase, and the internal structure is prone to uneven force and damage when laid over a large area. Summary of the invention

[0003] Technical problem to be solved: In order to solve the above technical problems, the present invention provides a straw board for floor slabs and a manufacturing method and application thereof, which can improve the mechanical properties of the board while reducing the amount of adhesive applied. At the same time, the product has hydrophobicity and fire resistance, and is easy to process and shape secondaryly.

[0004] Technical solution: A method for manufacturing a straw board for floor slabs, comprising the following steps: (1) washing rice straw with water, drying it, crushing it with a pulverizer, and oscillating and screening it to obtain small segments of 1-3 mm to obtain straw crushed material; (2) taking the straw crushed material, stirring and washing it in water for 30-60 minutes to remove solid impurities remaining in the straw crushing process; extruding and dehydrating the washed straw, and then drying it; (3) adding the straw crushed material to a sodium hydroxide solution, soaking it at room temperature for 30-70 minutes under the condition of an ultrasonic power of 300-900 W, washing it with deionized water until the washing liquid is neutral, draining it, soaking it in a sulfuric acid solution with a mass fraction of 15-35wt.% at room temperature for 20-40 minutes, and then washing it with deionized water until the washing liquid is neutral. The straw fibers are then soaked in a 5-15wt.% sodium silicate solution for 10-20 minutes, and finally dried to obtain straw fibers, and then a hydrophobic material and a modifier are added to the straw fibers, wherein the sum of the amount of the hydrophobic material added does not exceed 5% of the mass of the straw fibers, and the sum of the amount of the modifier added does not exceed 5% of the mass of the straw fibers; (4) the straw fibers obtained in step (3) are fed into a stirring type glue sprayer, wherein a spray gun is provided in the stirring type glue sprayer for glue spraying, and the amount of glue applied is 7-15% of the mass of the straw fed into the stirring type glue sprayer, and the glue material is diphenylmethane diisocyanate adhesive (MDI) , stirring to evenly mix the straw fiber and the adhesive; (5) transferring the straw fiber mixed with the adhesive in step (4) to a molding machine, and performing pre-pressing and hot pressing in the molding machine after paving, and then program cooling, taking out the board and performing edge trimming, sanding, etc.; wherein the pre-pressing conditions are: temperature of 90-110°C, heating rate of 5°C / min, pressure of 3.0-5.0MPa, and hot pressing time of 8-12 minutes; the hot pressing conditions are: temperature of 150-170°C, pressure of 7.0-12.0MPa, heating rate of 5°C / min, and hot pressing time of 8-12 minutes, to obtain a straw board.

[0005] Preferably, the concentration of the sodium hydroxide solution is 2wt.%, and the amount of sodium hydroxide used is 0.5% of the mass of the straw; the concentration of the sulfuric acid solution is 20wt.%.

[0006] Preferably, the concentration of the sodium silicate solution is 10 wt.%.

[0007] Preferably, the hydrophobic materials are perfluoroacrylic copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate, and the added amounts of perfluoroacrylic copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate are 1wt.%, 0.5wt.% and 2.5wt.% of the straw fiber, respectively; the modifier is hydroxymethyl cellulose or graphene oxide, and the added amounts of hydroxymethyl cellulose and graphene oxide are 2wt.% and 3wt.% of the straw fiber, respectively.

[0008] Preferably, the diphenylmethane diisocyanate adhesive (MDI) contains 10 wt.% of epoxy soybean oil maleimide and 5 wt.% of an amine curing agent, wherein the amine curing agent is polyetheramine (D-230), isophorone diamine (IPDA) and 3,3'-dimethyl-4,4'-diamino-dicyclohexylmethane (DMDC).

[0009] Preferably, the pre-pressing conditions are: temperature of 100°C, heating rate of 5°C / min, pressure of 4.0MPa, and hot pressing time of 10 minutes; the hot pressing conditions are: temperature of 160°C, pressure of 10.0MPa, heating rate of 5°C / min, and hot pressing time of 10 minutes to obtain straw board.

[0010] The straw board for floor slab is made by the above-mentioned manufacturing method.

[0011] The above straw board is used in manufacturing floor slabs.

[0012] The floor slab is composed of at least two layers of straw boards, one above and one below, a group of sound insulation units are arranged between the straw boards, an I-shaped connector is arranged between adjacent sound insulation units, the upper and lower ends of the I-shaped connector are respectively fixedly connected to the straw boards, one end of the straw board is movably connected to the wall, and the connecting end is provided with a cavity. The connecting end is a C-shaped buckle structure as a whole, wherein the upper straw board is provided with upper and lower protrusions, and a sliding steel ball is arranged below the end of the upper buckle structure; a depression is arranged below the lower straw board, and a sliding steel ball is arranged at the bottom of the lower buckle structure.

[0013] Beneficial effects: The straw board of the present invention has high strength as a whole, and has good flame retardancy after adding sodium silicate. Due to the small amount of addition, it has almost no effect on the physical and chemical properties of the synthetic material itself; after adding the hydrophobic material, the board also has good water resistance, and after adding the modifier hydroxymethyl cellulose, the performance of the board itself meets the corresponding requirements, avoiding the influence of the hydrophobic material on the product structure, realizing the efficient and high value-added recycling of plant straw, green and environmentally friendly, and having broad application prospects. The gelling agent added to the straw board of the present invention is diphenylmethane diisocyanate adhesive (MDI), which is non-toxic, tasteless, and formaldehyde-free. It not only has high stability, but also has zero formaldehyde emissions, and cuts off the formaldehyde emission problem from the source; and is evenly mixed with the straw raw material through a disperser, and the prepared board maintains high strength while being light in weight, which is convenient for transportation and construction and installation. Graphene oxide is added to the straw board prepared by the present invention, which can conduct heat more effectively in the hot pressing process, and can be bent to a limited extent after heating, and is suitable for cutting. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the floor structure. DETAILED DESCRIPTION

[0015] The following examples will enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0016] Example 1

[0017] The method for preparing the straw board of this embodiment comprises the following steps:

[0018] (1) Wash the rice straw with water, dry it in a dryer at 120°C to a moisture content of 15 wt.%, crush it in a pulverizer, and vibrate and sieve to obtain small segments of 1-3 mm to obtain straw crushed material;

[0019] (2) taking the straw crushed material, stirring and washing it in water for 60 minutes to remove the solid impurities remaining in the straw crushing process; squeezing and dehydrating the washed straw, and then drying it in a dryer at a temperature of 120°C to a moisture content of 15wt.%;

[0020] (3) Add the straw crushed material into a 2% sodium hydroxide solution (the amount of sodium hydroxide is 0.5% of the mass of the straw), soak it at room temperature for 60 minutes under the condition of ultrasonic power of 600W, wash it with deionized water until the washing liquid is neutral, drain it, soak it in a 20wt.% sulfuric acid solution at room temperature for 30 minutes, wash it with deionized water until the washing liquid is neutral, then soak it in a 10wt.% sodium silicate solution for 10-20 minutes, and finally dry it at 120℃ to obtain straw fiber, then add perfluoroacrylic copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate to the straw fiber, the addition amount of the perfluoroacrylic copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate is 1wt.%, 0.5wt.% and 2.5wt.% of the straw fiber respectively, then add hydroxymethyl cellulose and graphene oxide, the addition amount of the hydroxymethyl cellulose and graphene oxide is 2wt.% and 3wt.% of the straw fiber respectively;

[0021] (4) feeding the straw fiber obtained in step (3) into a stirring type glue sprayer, wherein a spray gun is provided in the stirring type glue sprayer for glue spraying, and the glue application amount is 10% of the mass of the straw fed into the stirring type glue sprayer, and the glue material is diphenylmethane diisocyanate adhesive (MDI), wherein the diphenylmethane diisocyanate adhesive (MDI) contains 10wt.% of epoxy soybean oil maleimide and 5wt.% of polyetheramine (D-230), and stirring is performed to uniformly mix the straw fiber and the adhesive;

[0022] (5) The straw fiber mixed with the adhesive in step (4) is transferred to a molding machine, and after laying, it is pre-pressed and hot-pressed in the molding machine, and then programmed to cool. After taking out the board, it is trimmed and sanded, etc.; wherein the pre-pressing conditions are: temperature of 100°C, heating rate of 5°C / min, pressure of 4.0MPa, and hot pressing time of 10 minutes; the hot pressing conditions are: temperature of 160°C, pressure of 10.0MPa, heating rate of 5°C / min, and hot pressing time of 10 minutes, to obtain a straw board.

[0023] The obtained straw board was tested and met the following indicators: fire resistance limit performance of 70min at 1200℃; sound insulation performance of 45dB; water absorption coefficient of 3%; ultimate pressure of 5.5Mpa / m 3 ; The impact strength test is carried out in accordance with GB / T 1843-1996, and the tensile strength test is carried out in accordance with GB / T 1446-2005, where the impact strength is 0.96KJ / m 2 The tensile strength is 0.5Mpa, the contact angle of the plate surface is 155°, the rolling angle is 3.5°, it will not foam or loosen under water conditions for 24 months, and there will be no peeling or quality loss when the plate is heated and bent.

[0024] Example 2

[0025] The method for preparing the straw board of this embodiment comprises the following steps:

[0026] (1) Wash the rice straw with water, dry it in a dryer at 120°C to a moisture content of 15 wt.%, crush it in a pulverizer, and vibrate and sieve to obtain small segments of 1-3 mm to obtain straw crushed material;

[0027] (2) taking the straw crushed material, stirring and washing it in water for 60 minutes to remove the solid impurities remaining in the straw crushing process; squeezing and dehydrating the washed straw, and then drying it in a dryer at a temperature of 120°C to a moisture content of 15wt.%;

[0028] (3) Add the straw crushed material into a 2% sodium hydroxide solution (the amount of sodium hydroxide is 0.5% of the mass of the straw), soak it at room temperature for 60 minutes under the condition of ultrasonic power of 600W, wash it with deionized water until the washing liquid is neutral, drain it, soak it in a 20wt.% sulfuric acid solution at room temperature for 30 minutes, wash it with deionized water until the washing liquid is neutral, then soak it in a 10wt.% sodium silicate solution for 10-20 minutes, and finally dry it at 120℃ to obtain straw fiber, then add perfluoroacrylic copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate to the straw fiber, the addition amount of the perfluoroacrylic copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate is 1wt.%, 0.5wt.% and 2.5wt.% of the straw fiber respectively, and then add graphene oxide, the addition amount of the graphene oxide is 3wt.% of the straw fiber;

[0029] (4) feeding the straw fiber obtained in step (3) into a stirring type glue sprayer, wherein a spray gun is arranged in the stirring type glue sprayer for glue spraying, and the glue application amount is 10% of the mass of the straw fed into the stirring type glue sprayer, and the glue material is diphenylmethane diisocyanate adhesive (MDI), wherein the diphenylmethane diisocyanate adhesive (MDI) contains 10wt.% of epoxy soybean oil maleimide and 5wt.% of polyetheramine (D-230), and stirring is performed to uniformly mix the straw fiber and the adhesive;

[0030] (5) The straw fiber mixed with the adhesive in step (4) is transferred to a molding machine, and after laying, it is pre-pressed and hot-pressed in the molding machine, and then programmed to cool. After taking out the board, it is trimmed and sanded, etc.; wherein the pre-pressing conditions are: temperature of 100°C, heating rate of 5°C / min, pressure of 4.0MPa, and hot pressing time of 10 minutes; the hot pressing conditions are: temperature of 160°C, pressure of 10.0MPa, heating rate of 5°C / min, and hot pressing time of 10 minutes, to obtain a straw board.

[0031] The obtained straw board was tested and met the following indicators: fire resistance limit performance of 70min at 1200℃; sound insulation performance of 45dB; water absorption coefficient of 3%; ultimate pressure of 5.5Mpa / m 3 ; The impact strength test is carried out in accordance with GB / T 1843-1996, and the tensile strength test is carried out in accordance with GB / T 1446-2005, where the impact strength is 0.90KJ / m 2 The tensile strength is 0.4Mpa, the contact angle of the plate surface is 154.5°, the rolling angle is 3.0°, and the foam becomes loose after 10 months of immersion in water. When the plate is heated and bent, there is flaking on the surface and fracture lines on the bent part.

[0032] Example 3

[0033] The method for preparing the straw board of this embodiment comprises the following steps:

[0034] (1) Wash the rice straw with water, dry it in a dryer at 120°C to a moisture content of 15 wt.%, crush it in a pulverizer, and vibrate and sieve to obtain small segments of 1-3 mm to obtain straw crushed material;

[0035] (2) taking the straw crushed material, stirring and washing it in water for 30 minutes to remove the solid impurities remaining in the straw crushing process; squeezing and dehydrating the washed straw, and then drying it in a dryer at a temperature of 120°C to a moisture content of 15wt.%;

[0036] (3) Add the straw crushed material into a 2% sodium hydroxide solution (the amount of sodium hydroxide is 0.5% of the mass of the straw), soak it at room temperature for 60 minutes under the condition of ultrasonic power of 400W, wash it with deionized water until the washing liquid is neutral, drain it and soak it in a 20wt.% sulfuric acid solution at room temperature for 30 minutes, wash it with deionized water until the washing liquid is neutral, then soak it in a 10wt.% sodium silicate solution for 15 minutes, and finally dry it at 120℃ to obtain straw fiber, then add perfluoroacrylic copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate to the straw fiber, the addition amount of the perfluoroacrylic copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate is 1wt.%, 0.5wt.% and 2.5wt.% of the straw fiber respectively, then add hydroxymethyl cellulose and graphene oxide, the addition amount of the hydroxymethyl cellulose and graphene oxide is 3wt.% and 2wt.% of the straw fiber respectively;

[0037] (4) feeding the straw fiber obtained in step (3) into a stirring glue sprayer, wherein a spray gun is arranged in the stirring glue sprayer for glue spraying, and the glue application amount is 10% of the mass of the straw fed into the stirring glue sprayer, and the glue material is diphenylmethane diisocyanate adhesive (MDI), wherein the diphenylmethane diisocyanate adhesive (MDI) contains 10wt.% of epoxy soybean oil maleimide and 5wt.% of amine curing agent polyetheramine (D-230), and stirring is performed to uniformly mix the straw fiber and the adhesive;

[0038] (5) The straw fiber mixed with the adhesive in step (4) is transferred to a molding machine, and after laying, it is pre-pressed and hot-pressed in the molding machine, and then programmed to cool. After taking out the board, it is trimmed and sanded, etc.; wherein the pre-pressing conditions are: temperature of 110°C, heating rate of 5°C / min, pressure of 5.0 MPa, and hot pressing time of 12 minutes; the hot pressing conditions are: temperature of 170°C, pressure of 12.0 MPa, heating rate of 5°C / min, and hot pressing time of 12 minutes, to obtain a straw board.

[0039] The obtained straw board was tested and met the following indicators: fire resistance limit performance 90min at 1200℃; sound insulation performance 32dB; water absorption coefficient 2.5%; ultimate pressure 6.5Mpa / m 3 ; The impact strength test is carried out in accordance with GB / T 1843-1996, and the tensile strength test is carried out in accordance with GB / T 1446-2005, where the impact strength is 1.2KJ / m 2 The tensile strength is 0.9Mpa, the contact angle of the plate surface is 157°, the rolling angle is 4°, it will not foam or loosen for 36 months under water immersion conditions, there will be no peeling or quality loss when heated and bent, and there will be no cracks in the bent part.

[0040] Example 4

[0041] The straw board described in Example 1 or 3 is used in manufacturing a floor slab. The floor slab is composed of two layers of straw board, a group of sound insulation units 1 is provided between the straw board, and an I-shaped connector 2 is provided between adjacent sound insulation units 1. The upper and lower ends of the I-shaped connector 2 are respectively fixedly connected to the straw board, one end of the straw board is movably connected to the wall 3, and the connecting end is provided with a cavity 4. The connecting end is a C-shaped buckle structure as a whole, wherein the upper straw board is provided with upper and lower protrusions 5, and a sliding steel ball 6 is provided below the end of the upper buckle structure; a depression 7 is provided below the lower straw board, and a sliding steel ball is provided at the bottom of the lower buckle structure. The sliding steel ball can be used to conveniently connect the floor slab to the wall, and the buckle structure and the protrusion and depression structure thereon can more stably connect the floor slab to the wall.

Claims

1. A method for manufacturing a straw board for floor slab, characterized in that The steps are as follows: (1) washing the rice straw with water, drying it, crushing it with a crusher, and vibrating and screening it to obtain 1- 3mm small segments to obtain straw crushed material; (2) taking the straw crushed material, stirring and washing it in water for 30-60min to remove the solid impurities remaining in the straw crushing process; squeezing and dehydrating the washed straw, and then drying it; (3) adding the straw crushed material to a sodium hydroxide solution, soaking it at room temperature for 30-70 minutes under the condition of an ultrasonic power of 300-900W, washing it with deionized water until the washing liquid is neutral, draining it, soaking it in a sulfuric acid solution with a mass fraction of 15-35wt.% at room temperature for 20-40 minutes, then washing it with deionized water until the washing liquid is neutral, and then soaking it in a 5-15wt.% sodium silicate solution for 10-20 minutes, and finally drying it to obtain straw fiber, and then adding a hydrophobic material and a modifier to the straw fiber, wherein the sum of the added amount of the hydrophobic material does not exceed 5% of the mass of the straw fiber, and the sum of the added amount of the modifier does not exceed 5% by mass; (4) feeding the straw fiber obtained in step (3) into a stirring type glue sprayer, wherein a spray gun is arranged in the stirring type glue sprayer for glue spraying, and the glue application amount is 7-15% of the mass of the straw fed into the stirring type glue sprayer, and the glue material is diphenylmethane diisocyanate adhesive, and the straw fiber and the adhesive are stirred to be uniformly mixed; (5) transferring the straw fiber mixed with the adhesive in step (4) into a molding machine, and after paving, pre-pressing and hot pressing are performed in the molding machine, and then programmed cooling is performed, and the board is taken out and trimmed and sanded; wherein the pre-pressing conditions are: temperature of 90-110°C, heating rate of 5°C / min, pressure of 3.0-5.0MPa, and hot pressing time of 8-12 minutes; and the hot pressing conditions are: temperature of 150-170°C, pressure of 7.0-12.0MPa, heating rate of 5°C / min, and hot pressing time of 8-12 minutes, to obtain a straw board.

2. The method for manufacturing the straw board for floor slab according to claim 1, characterized in that The concentration of the sodium hydroxide solution is 2wt.%, and the amount of sodium hydroxide used is 0.5% of the mass of the straw; the concentration of the sulfuric acid solution is 20wt.%.

3. The method for manufacturing the straw board for floor slab according to claim 1, characterized in that The concentration of the sodium silicate solution is 10 wt.%.

4. The method for manufacturing the straw board for floor slab according to claim 1, characterized in that The hydrophobic material is a perfluoroacrylic acid copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate, and the addition amounts of the perfluoroacrylic acid copolymer surfactant, F-1061 fluorosilane and hydroxyethyl methacrylate account for 1wt.%, 0.5wt.% and 2.5wt.% of the straw fiber respectively; the modifier is hydroxymethyl cellulose or graphene oxide, and the addition amounts of hydroxymethyl cellulose and graphene oxide account for 2wt.% and 3wt.% of the straw fiber respectively.

5. The method for manufacturing the straw board for floor slab according to claim 2, characterized in that The diphenylmethane diisocyanate adhesive contains 10 wt.% of epoxy soybean oil maleimide and 5 wt.% of an amine curing agent, wherein the amine curing agent is polyetheramine, isophorone diamine and 3,3'-dimethyl-4,4'-diamino-dicyclohexylmethane.

6. The method for manufacturing the straw board for floor slab according to claim 1, characterized in that The pre-pressing conditions are: temperature of 100°C, heating rate of 5°C / min, pressure of 4.0MPa, and hot pressing time of 10 minutes; the hot pressing conditions are: temperature of 160°C, pressure of 10.0MPa, heating rate of 5°C / min, and hot pressing time of 10 minutes to obtain straw board.

7. Straw board material for floor slabs produced by the manufacturing method according to any one of claims 1 to 6.

8. Use of the straw board material according to claim 7 in manufacturing floor slabs.

9. The use according to claim 8, characterized in that The floor slab is composed of at least two layers of straw board, one above the other; a group of sound insulation units (1) is provided between the straw board; an I-shaped connecting piece (2) is provided between adjacent sound insulation units (1); upper and lower ends of the I-shaped connecting piece (2) are respectively fixedly connected to the straw board; one end of the straw board is movably connected to a wall (3); and a cavity (4) is provided at the movably connected connecting end.

10. The use according to claim 9, characterized in that The connecting end is a C-shaped buckle structure as a whole, wherein the upper straw board is provided with upper and lower protrusions (5), and the upper straw board is provided with a sliding steel ball (6) below the end of the buckle structure; the lower straw board is provided with a recess (7) below, and the lower straw board is provided with a sliding steel ball at the bottom of the buckle structure.

Citation Information

Patent Citations

  • Environment-friendly light heat-insulating material and manufacturing method thereof

    CN102180639A

  • AU2703188A